Low-Dose Gamma-Radiation Inhibits Benzo[a]pyrene-Induced Lung Adenoma Development in A/J Mice - Veronica R. Bruce; Steven A. Belinsky; Katherine Gott; Yushi Liu; Thomas March; Bobby Scott; Julie Wilder (SAGE Publishing, 2012)
Low-dose ionizing radiation (LDR) may lead to suppression of smoking-related lung cancer. We examined the effects of a known cigarette smoke carcinogen Benzo[a]pyrene (B[a]P) alone or in combination with fractionated low-dose gamma radiation (60 - 600 mGy total dose) on the induction of lung neoplasms in the A/J mouse. Our results show that 600 mGy of gamma radiation delivered in six biweekly fractions of 100 mGy starting 1 month after B[a]P injection significantly inhibits the development of lung adenomas per animal induced by B[a]P. Our data also indicated that the six biweekly doses suppressed the occurrence of spontaneous hyperplastic foci in the lung, although this suppression failed to reach statistical significance when analyzed as average foci per lung possibly related to the small sample sizes used for the control and test groups.